2021
DOI: 10.21037/atm-20-8093
|View full text |Cite|
|
Sign up to set email alerts
|

Huperzine A lowers intraocular pressure via the M3 mAChR and provides retinal neuroprotection via the M1 mAChR: a promising agent for the treatment of glaucoma

Abstract: Background: Glaucoma is a neurodegenerative disease that shares similar pathological mechanisms with Alzheimer's disease (AD). Drug treatments for glaucoma increasingly rely upon both lowering of intraocular pressure (IOP) and optic nerve protection, as lowering of IOP alone has been unsatisfactory. Huperzine A (HupA) is an acetylcholinesterase inhibitor (AChEI) used for AD. This study investigated the potential of HupA as a treatment for glaucoma. Methods:The ability of HupA to lower IOP via causing pupil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Retinal I/R injury is a pathophysiological process of glaucoma [ 5 ]. If an effective treatment is not provided, it may cause the loss of retinal function and eventually lead to blindness [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal I/R injury is a pathophysiological process of glaucoma [ 5 ]. If an effective treatment is not provided, it may cause the loss of retinal function and eventually lead to blindness [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that retinal blood supply disorder, reperfusion injury, and nutritional deficiency caused by elevated IOP are considered to be the most important risk factors for the occurrence and development of glaucoma [ 4 ]. However, progressive optic nerve injury still occurs in some patients after drug intervention, laser therapy, or surgical treatment, which are only aimed to reduce IOP [ 5 ]. Therefore, in this case, it is urgent to find effective drugs that protect vision by preventing the death of retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…Latanoprost-prostaglandin analogues have demonstrated neuroprotective effects on glutamate-induced RGC death and axotomy-induced ocular neuropathy in animal models, in addition to significantly lowering IOP [ 98 ]. Latanoprost is a glutamate inhibitor and it also inhibits hypoxia-induced apoptosis and functions through cyclooxygenase-2 pathway in order to achieve its neuroprotective benefits [ 99 ].…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…Additionally, activation of PKC delta was suggested to regulate neurotrophin levels by M 1 muscarinic receptor activation ultimately leading to an increase in RGCs’ survival in vitro in the retina [ 89 , 90 ]. In 2021, an in vivo study in rats showed that huperzine A lowers intraocular pressure via the M 3 receptor and exerts neuroprotective effects in the retina by increasing endogenous ACh levels and activating M 1 receptors and their downstream AKT/MAPK signaling pathways [ 31 ].…”
Section: Functional Roles Of Individual Machr Subtypes In the Retinamentioning
confidence: 99%
“…However, M 2 and M 4 receptors have been shown to preferentially couple to G proteins of the Gi and Go family [ 3 , 29 ]. Some studies reported that mAChR agonists reduce IOP and exert neuroprotective effects in glaucoma [ 30 , 31 , 32 ]. The non-subtype-selective mAChR antagonist, atropine, has been shown to inhibit scleral proliferation and matrix synthesis, and to prevent axial elongation of the eyeball providing a novel therapeutic approach for myopia control [ 14 , 33 ].…”
Section: Introductionmentioning
confidence: 99%